Sensorial Investigations A History of the Senses in Anthropology, Psychology, and Law - Howes, David (Perspectives on Sensory History, 2023)
David Howes's sweeping history of the senses in the disciplines of anthropology and psychology and in the field of law lays the foundations for a sensational jurisprudence, or a way to do justice to and by the senses of other people.In part 1, Howes demonstrates how sensory ethnography has yielded alternative insights into how the senses function and argues convincingly that each culture should be approached on its own sensory terms. Part 2 documents how the senses have been disciplined psychologically within the Western tradition, starting with Aristotle and moving through the rise of Lockean empiricism and cognitive neuroscience. Here, Howes presents an anthropologically informed critique of experimental and cognitive psychology, sensory science, and phenomenology. In part 3, he introduces the paradigm of the "historical anthropology of the senses and sensation" and applies it to the analysis of trade relations between Europe and China in the early modern period, to the treaty-making process in North America during the colonial period, and to all the unresolved disputes over land rights and Indigenous sovereignty that continue to this day, arguing that these differences are rooted in a cultural clash of sensoria.Designed for the classroom, Sensorial Investigations displays an expansive critical engagement with generations of scholarship. It is essential reading for students and scholars of the history and anthropology of the senses, the psychology of sensation, and socio-legal studies